Replacement Rates and the Retirement Crisis - Andrew G. Biggs (American Enterprise Institute (AEI), 2023)
In 2014, the annual Social Security Trustees Report removed measures of Social Security replacement rates, which represent Social Security retirement benefits as a percentage of pre-retirement earnings. The Trustees expressed concerns that the Social Security Administration's (SSA) actuaries' methodology produced results that differed meaningfully from other common approaches. In 2023, the Social Security Trustees returned replacement rates to the report, without changes to the SSA methodology or discussion of their decision. The SSA replacement rate methodology produces the well-known result that Social Security replaces about 40 percent of a "medium wage" worker's pre-retirement earnings. However, that calculation is based upon a stylized worker whose annual earnings as represented in the replacement rate calculation are 42 percent higher than the inflation-adjusted career-average earnings of a worker with an average age-earnings profile. For a worker who earned the age-adjusted average wage, Social Security replaces about 54 percent of the final 35 years of inflation-adjusted earnings, a roughly one-quarter increase relative to the SSA's figures. Moreover, the difference between the SSA's replacement rates and those measured relative to inflation-adjusted career-average earnings grows when the assumed rate of real wage growth is higher. This is significant for projections of future retirement income adequacy, as the Trustees project future wage growth that exceeds what many past cohorts of Social Security participants experienced. Using a SSA projection of total retirement incomes from all sources, it is shown that a projected increase in the share of retirees with low replacement rates is a product of these assumptions. When replacement rates are measured relative to career-average earnings adjusted for inflation, future cohorts of seniors are projected to have similar replacement rates to past and present retirees.
Keywords: 330